Food tourism around the world : development, management and markets - Hall, Colin Michael, 1961- (Elsevier Butterworth-Heinemann, 2004)
Food and wine are vital components of the tourism experience, and are increasingly being seen as prime travel motivators in their own right. Food Tourism Around The World: Development, Management and Markets offers a unique insight into this phenomenon, looking at the interrelationship between food, the tourism product and the tourist experience. Using international case studies and examples from Europe, North America, Australasia and Singapore, Food Tourism Around The World: Development, Management and Markets discusses the development, range and repurcussions of the food tourism phenomenon.